International Standards of Penitentiary Activity: Impact on the Development of the Penitentiary Activity of the CIS Countries - S. Burtsev, Andrey; I. Ivanenko, Yaroslav; A. Kupryashina, Elena; V. Mironuk, Ivan; N. Omelin, Victor (International Journal of Criminology and Sociology, 2022)
Overcrowding in prisons is a common problem that affects many countries. It is difficult to define this term because there is no single internationally accepted standard. This article presents a comparative study of international standards for the activities of doctors in penitentiary institutions as an integral part of international standards of penitentiary activity. The authors investigated the methods and the degree of their impact on the penitentiary legislation of the Russian Federation and other CIS countries. The conclusion is drawn about the positive role of such standards in improving the national penitentiary legislation in order to increase the level of medical care for prisoners.